2017
DOI: 10.1515/npf-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Two-Legged Stool: New Findings from California on Nonprofits and Overhead

Abstract: Nonprofit overhead is a prevalent and controversial topic in the nonprofit and philanthropic sector. Online raters (such as Charity Navigator) point to the overhead rate as a key indicator of nonprofit worthiness. Different government entities use wildly different indirect cost rates when contracting with nonprofits, which translate into billions of dollars of funding being gained or lost. Foundations rarely have explicit guidelines, but most have informal rules of thumb that affect how a nonprofit can use gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 6 publications
(16 reference statements)
1
12
0
Order By: Relevance
“…The Nonprofit Overhead Costs Project reported that nonprofits felt the highest pressure from government funders to limit their administrative costs, much higher than from other constituents including watchdogs, donors, and foundations (Wing & Hager, 2004). A similar finding was also documented in a recent survey of California nonprofits (Berlin et al, 2017). In sum, in the price line of reasoning, if government wants its dollar to maximize program output, organizations asking for lower administrative costs would be preferred.…”
Section: Theoretical Frameworksupporting
confidence: 88%
See 2 more Smart Citations
“…The Nonprofit Overhead Costs Project reported that nonprofits felt the highest pressure from government funders to limit their administrative costs, much higher than from other constituents including watchdogs, donors, and foundations (Wing & Hager, 2004). A similar finding was also documented in a recent survey of California nonprofits (Berlin et al, 2017). In sum, in the price line of reasoning, if government wants its dollar to maximize program output, organizations asking for lower administrative costs would be preferred.…”
Section: Theoretical Frameworksupporting
confidence: 88%
“…When acquiring services from nonprofits, to maximize the proportion of funding devoted to programs, government presumably sets high (and sometimes unrealistic) expectations to push nonprofits to keep administrative costs down. A widely used practice is to set caps to severely limit the percentages of funding that can be used for administrative purposes (Berlin et al, 2017; GAO, 2010). This emphasis on efficiency in government procurements leads nonprofits to overlook the improvement of their infrastructure and operations, which further compromises their organizational effectiveness and service quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen (2016) argues that this holds true for major donors in particular who are more likely than small donors to pay attention to organizational performance metrics. Accordingly, managers have been found to perceive donor pressure to contain overhead costs which impacts their willingness to engage in ratio management (Berlin et al, 2017;Parsons et al, 2017). Following these prior studies, we hypothesize: Hypothesis 1 (H1): Nonprofit financial managers exposed to donor pressure will show a higher level of overhead-decreasing ratio management behavior than decision makers who are not exposed to pressure.…”
Section: Donor Pressurementioning
confidence: 93%
“…Nonprofits' administrative efficiency has received increasing scholarly and practical attention in recent years (e.g., Ashley & Van Slyke, 2012;Berlin, Masaoka, & Schumann, 2017;Chikoto & Neely, 2014;Eckhart-Queenan, Etzel, & Prasad, 2016;Tinkelman & Mankaney, 2007). The implicit assumption in this body of literature is that society does not favor nonprofits' high AERs because organizations with more administrative expenses may not maximize their program outputs, which undermines their capacity to advance charitable purposes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%